DEVELOPING MATERIALS ENGLISH TEXTBOOK “SMART ENGLISH” FOR THE FIFTH GRADE OF ELEMENTARY SCHOOL - Azkya Jamila (Language-Edu, 2020)
AbstractEnglish has become an extracurricular in Elementary school. In Elementary school, students need to increase their their English knowledge. Students should have textbook  English material which is appropriate with their life.  This research conducted to develope an English material textbook for grade V students of Elementary school in Malang. The title book is “Smart English” for students Grade V of Elementary School. In this texbook, the researcher focused on developing book related to curriculum 2013. The material explained on the product was about the material that relate to the students’ life. the material was used an integrated skill in each unit.  This product focused to the students character buiding, in the textbook material the researcher develops material using an embedded message in each units.  This product gave the additional material to help the students in learning English. The researcher did the needs analysis to identify the problems. Then proceed with the products development; begin with deciding the title for each unit and the material, and also give some pictures and exercises. The validation done and obtain some feedback for some revision before the tryout to the small group of the students. This product was better than the previous, it was because sometimes thebook does not appropriate with the students’ needs. Therefore, this book focused on English material with the students’ need in Elementary school. Key Words: Elementary School, Textbook, Moral Value